Conservantes Naturales para la Industria Cárnica - Llugsa Guananga, Ana Gabriela (2017)
Now a day, the natural preservatives are such an important system into the industrial products that guarantee trust in costumers. The present project has as a purpose to elaborate sausage (salami) of quality with natural additives such essential oil (rosemary and lemon) that have vitamins and increase the body strength. Also with this research, people are going to take advantage of natural additives with two types of oil which was made as the next way: washing and disinfected of the equipment, reception of feedstock, cut up, weight up. It was evaluated by students of the agroindustry career through surveys in order to know the main characteristics of the product as taste, texture, color and checking that the best treatment was the 6% of lemon essential oil. The results of the physical - chemistry analysis of the best treatment were 10,30% ash, 21%50 humidity, 36.60%fat, 35.50% protein,0,329% dietary fiber, total carbohydrates 0%. The cost of the production of salami is 9.60 dollars per each pound of salami and the essential oil extraction of each 10ml bottle $11.10.